2011
DOI: 10.1002/aic.12655
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced lipid and biodiesel production from glucose‐fed activated sludge: Kinetics and microbial community analysis

Abstract: An innovative approach to increase biofuel feedstock lipid yields from municipal sewage sludge via manipulation of carbon-to-nitrogen (C:N) ratio and glucose loading in activated sludge bioreactors was investigated. Sludge lipid and fatty acid methyl ester (biodiesel) yields (% cell dry weight, CDW) were enhanced via cultivation in activated sludge bioreactors operated at high initial C:N ratio (!40:1) and glucose loading (!40 g L À1 ). Under C:N 70, 60 g L À1 glucose loading, a maximum of 17.5 AE 3.9 and 10.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 33 publications
4
52
2
Order By: Relevance
“…These reductions that occurred while xylose consumption appeared to stall in the first 24 h could be attributed to the acclimation of the activated sludge microorganisms to xylose by synthesis of enzymes for xylose utilization or by the shifting of the microbial population, in which a fraction of the microorganisms more acclimated for xylose utilization proliferated and dominated while others declined similar to the results of our previous investigation. 24 Growth and lipid accumulation then commenced to reach average maximum levels of 14 and 3.2 g/L of non-lipid biomass and lipid, respectively. Over the course of these experiments, an average maximum lipid content of 21.5 6 3.6% CDW of the enhanced sludge was achieved, which is more than twice as much the initial lipid content of raw activated sludge and higher than those achieved when using glucose as sole carbon source.…”
Section: Fermentation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…These reductions that occurred while xylose consumption appeared to stall in the first 24 h could be attributed to the acclimation of the activated sludge microorganisms to xylose by synthesis of enzymes for xylose utilization or by the shifting of the microbial population, in which a fraction of the microorganisms more acclimated for xylose utilization proliferated and dominated while others declined similar to the results of our previous investigation. 24 Growth and lipid accumulation then commenced to reach average maximum levels of 14 and 3.2 g/L of non-lipid biomass and lipid, respectively. Over the course of these experiments, an average maximum lipid content of 21.5 6 3.6% CDW of the enhanced sludge was achieved, which is more than twice as much the initial lipid content of raw activated sludge and higher than those achieved when using glucose as sole carbon source.…”
Section: Fermentation Experimentsmentioning
confidence: 99%
“…Sludge biomass with increased lipid content and biodiesel yield of around 17.5 6 3.9 wt % and 10.2 6 2.0 wt %, respectively were generated-significantly higher than those obtained from raw sewage activated sludge. 24 Additionally, molecular analysis established that the increased oil content of the sludge could be attributed to a population shift in the activated sludge microbial community toward microorganisms that could potentially exhibit oleaginous behavior but are yet to be identified. 24 This process could pose the following cost advantages: Using mixed cultures such as activated sludge could eliminate the need for media sterilization and assist in the implementation of continuous cultures with minimal risk of contamination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodiesel yield and fatty acid profile of the lipid extracts were estimated by a transesterification and gas chromatography-flame ionization detection (GC-FID) analysis method described in an earlier paper. 20 Residual acetic acid concentrations in the culture were measured using solvent extraction and subsequent analysis of the extracts by GC-FID based on a method described elsewhere. 27 Fermentation broth supernatant samples (0.5 mL) were transferred into microcentrifuge tubes and acidified by the addition of 0.5 mL of 50% (v/v) H 2 SO 4 in order to shift the acetic acid dissociation equilibrium towards the formation of the protonated acid which is more hydrophobic.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, our group has demonstrated the novel application of activated sludge microbial cultures obtained from municipal sewage treatment plants to produce biofuel feedstock lipids. 20 The cost advantages of using mixed cultures such as activated sludge include eliminating the need for media sterilization and the implementation of continuous cultures with minimal risk of contamination. 21 Therefore, the objective of this study was to determine the effect of acetic acid on growth and lipid accumulation by activated sludge microbial communities using glucose as the primary carbon source.…”
Section: Introductionmentioning
confidence: 99%